Enhanced Variable Stiffness and Variable Stretchability Enabled by Phase‐Changing Particulate Additives. (3rd October 2019) - Buckner, Trevor L.; Yuen, Michelle C.; Kim, Sang Yup; Kramer‐Bottiglio, Rebecca
Abstract: A novel phase‐changing particulate that amplifies a composite's modulus change in response to thermal stimulus is introduced. This particulate additive consists of a low melting point alloy (Field's metal; FM) formed into microparticles using a facile fabrication method, which enables its incorporation into polymer matrices using simple composite manufacturing processes. The effect of the solid–liquid phase change of the FM particles is demonstrated in two host materials: a thermally responsive epoxy and a silicone elastomer. In the epoxy matrix, this thermal response manifests as an amplified change in flexural modulus when heated, which is highly desirable for stiffness‐changing move‐and‐hold applications. In the silicone matrix, the stretchability can be switched depending on the phase of the FM particles. This phenomenon allows the silicone to stretch and hold a strained configuration, and gives rise to mechanically programmable anisotropy through reshaping of the FM inclusions. FM particles present many opportunities where on‐demand tunable modulus is required, and is particularly relevant to soft robotics. Because the melting temperature of FM is near room temperature, triggering the phase change requires low power consumption. The utility of FM particle‐containing composites as variable stiffness and variable stretchability elements for soft robotic applications is demonstrated. Abstract : Particles of low melting point alloys can be leveraged to create a new class of functional, responsive composite materials. Here, the solid–liquid phase change of Field's metal particles is used to amplify the range of stiffness modulation in an epoxy, and to create on‐demand switchable stretchability and mechanically programmable anisotropy in a silicone elastomer.